I want to die but I want to eat tteokbokki - Paek, Se-hui, 1990- (New York : Bloomsbury Publishing, 2023)
"A successful young social media director at a publishing house chronicles her ten years of psychiatric treatment for depression and she fought back against the harmful behaviors that kept her locked in a cycle of self-abuse"--
Keywords: Baek, Sehee; Depression; Depressed persons -- Korea (South) -- Biography; Depression, Mental -- Korea (South) -- Biography; Psychotherapy patients -- Korea (South) -- Biography; Mental health counseling -- Korea (South).